Association between consumption of soy and risk of cardiovascular disease: A meta-analysis of observational studies. (29th August 2020) - Yan, Zhaoli; Zhang, Xinyue; Li, Chunlin; Jiao, Shouchun; Dong, Wenyao
Abstract: Background: The relationships between dietary intake of soy foods and risk of cardiovascular disease are uncertain. The aims of this study were to evaluate and summarize the evidence on the association between consumption of soy and risk of cardiovascular disease (including stroke and coronary heart disease). Methods: We systematically searched the MEDLINE and EMBASE databases from their inception up to 22 February 2016. We included only observational studies, and used random-effects models to calculate summary relative risks (SRRs) and 95% confidence intervals (CIs). Results: A total of 10 prospective cohort and seven case-control studies met the inclusion criteria. There were a total of 17, 269 cardiovascular disease events, including 6265 stroke events, 10, 806 coronary heart disease events, and 198 other cardiovascular disease events. A significant negative association was shown between soy intake and risk of cardiovascular disease (SRR = 0.84 95% CI: 0.75–0.94; p heterogeneity <0.001, I 2  = 71.4%). Subgroup meta-analyses indicated that a statistically significant protective effect was primarily observed in case-control studies and in Asian populations. There was a borderline significant association between intake of tofu and the risk of cardiovascular disease (SRR = 0.80, 95% CI: 0.64–1.00). A significant negative association was shown for the association between soy intake and risk of stroke (SRR = 0.82, 95% CI: 0.68–0.99) and coronary heart disease (SRR = 0.83, 95% CI: 0.72–0.95). There were no associations between soy isoflavones consumption and risk of cardiovascular disease, stroke, and coronary heart disease. Conclusion: Overall evidence indicated that consumption of soy was negatively associated with the risk of cardiovascular disease, stroke, and coronary heart disease risk.